EFEKTIVITAS BAHAN AJAR SOSIOLINGUISTIK BERBANTUAN GAMMA.APP TERHADAP KOMPETENSI SOSIAL BAHASA MAHASISWA - Sari, Yuliana; Siallagan, Lasenna; Prasasti, Tri Indah (Universitas Hamzanwadi, 2025)
This study aims to determine the effectiveness of sociolinguistic teaching materials assisted by Gamma.app, which has been developed for use in the Indonesian Language and Literature Education Study Program at Unimed. This study uses the Research and Development (R&D) method. Data collection was conducted in three steps. First, observations were made to identify learning resources and materials. Second, questionnaires were distributed to faculty members and students to gather in-depth information about their needs in the learning process. Third, a specialized test was administered to students to measure the effectiveness of using Gamma.app-based instructional materials. The research results indicate that the sociolinguistics teaching materials assisted by Gamma.app are suitable for use, with an expert material validation score of 87.87% in the “very good” category and an expert media validation score of 89.92% in the “very good” category. Additionally, the product trial results based on student responses at 88.6% indicate that the developed product has been well-received by students and is effective in sociolinguistic learning to enhance students' social language competencies.